Effect of mexidol on lipid-phospholipid profile changes in elderly patients with stroke - Yu. V. Abramenko (Неврология, нейропсихиатрия, психосоматика, 2018)
Objective: to evaluate the efficiency of incorporating of mexidol into combination drug therapy for elderly patients with acute ischemic and hemorrhagic stroke (IS and HS). Patients and methods. Sixty patients aged 60 to 74 years with new-onset hemispheric stroke were examined. 34 patients of them were diagnosed with IS; 26 patients had intracerebral bleeding (ICB). A study group consisted of 31 patients who had taken mexidol in addition to therapy in accordance with the standards adopted in the Russian Federation. A comparison group included 29 patients who used only the standard therapy. Indicators were assessed using the National Institutes of Health Stroke Scale (NIHSS), the Riverbed mobility index, the modified Rankin scale, and the Barthel index before and during intravenous dropwise infusion of mexidol 500 mg for 10 days. The percentage absorption of lipidphospholipid complexes was also examined in the infrared spectrum of blood serum. A control group compromised 20 healthy individuals. Results and discussion. The time course of changes in the serum lipid-phospholipid complexes was found to correlate with the type of stroke. The incorporation of mexidol into combination drug therapy for elderly patients with the acute period of IS and ICB contributed to the regression of focal neurological deficit and to the improvement of daily activity and functional independence. Mexidol also exerted a positive effect on the level of neuronal membrane phospholipids. Conclusion. Mexidol was noted to have a positive effect on serum phospholipid levels. It is concluded that the incorporation of the drug into the combination therapy is effective in patients with acute IS and HS, in elderly people in particular.